Spider-girl. - DeFalco, Tom (Marvel Comics, 2005)
The adventures of Spider-Man's daughter continue as Mayday Parker faces defeat and disgrace at the hands of Darkdevil, the Avengers, and Kaine! Plus: Beset by problems in her civilian guise, Spider-Girl teams up with Speedball to take on Mr. Abnormal!